Learning Revitalization: MI Muhammadiyah Balung Teachers Welcome The E-Learning Era With Moodle - Soeharno, Ageng; Rizkika, Haressa Lintang; Siswanto, Edhi (Universitas Muhammadiyah Jember, 2023)
In this training, teachers are trained and supported to create additional web-based learning systems (e-learning) using LMS (Learning Management System). LMS is the most important tool in the teaching and learning process using software. This training uses an LMS, namely Moodle, which is based on open source code. Moodle is useful software for creating and delivering courses, used in training, and/or web-based education. The training was attended by 7 teachers from MI Muhammadiyah Balung. All participants are teachers, with areas of expertise in the technology group and the management and business group. The level of participation of participants who took part in the training was high as shown by their participation for two full days, participants showed their enthusiasm for associating information, especially related to e-learning creation and content development. The evaluation results in the form of independent assignments produced good results, where all participants were able to complete the assignments independently, with different durations for each participant